2008
DOI: 10.1519/jsc.0b013e31816611ea
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Types of Resisted Sprint Training Devices on the Kinematics of Sprinting at Maximum Velocity

Abstract: Resisted sprint running is a common training method for improving sprint-specific strength. For maximum specificity of training, the athlete's movement patterns during the training exercise should closely resemble those used when performing the sport. The purpose of this study was to compare the kinematics of sprinting at maximum velocity to the kinematics of sprinting when using three of types of resisted sprint training devices (sled, parachute, and weight belt). Eleven men and 7 women participated in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
3
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(157 citation statements)
references
References 12 publications
8
130
3
16
Order By: Relevance
“…Most studies that used these training methods to enhance sprint performance did so over several weeks [4][5][6]. Earlier studies suggested that resisted and assisted sprints increased muscular power output of the gluteus maximus, and the hip and knee extensors, and thereby stride length in normal sprints [7][8][9][10]. It is unclear whether resisted and assisted sprints can be effective as a part of complex training methods [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that used these training methods to enhance sprint performance did so over several weeks [4][5][6]. Earlier studies suggested that resisted and assisted sprints increased muscular power output of the gluteus maximus, and the hip and knee extensors, and thereby stride length in normal sprints [7][8][9][10]. It is unclear whether resisted and assisted sprints can be effective as a part of complex training methods [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, se ha estudiado que la dirección de la resistencia aplicada al atleta es diferente dependiendo del método de entrenamiento resistido usado. En consecuencia, cada método resistido tiene diferentes efectos sobre la velocidad del atleta y la mecánica del sprint (Alcaraz, Palao, Elvira & Linthorne, 2008) (Figura 1). Se ha documentado que el entrenamiento específico mejora la coordinación inter-muscular y asegura que el músculo está preparado para adquirir un mayor desarrollo de fuerza (Young, 2006).…”
Section: Definición De Métodos Resistidosunclassified
“…Por ejemplo, desde un punto de vista cinemático se recomiendan los arrastres de trineo con cargas altas y los sprints cuesta arriba para simular la fase de aceleración (Cronin & Hansen, 2006). El arrastre de trineo con cargas bajas (Alcaraz, Palao, Elvira & Linthorne, 2008), los chalecos y cinturones lastrados (Alcaraz, Palao, Elvira & Linthorne, 2008;Cronin & Hansen, 2006), y los paracaí-das de velocidad (Alcaraz, Palao, Elvira & Linthorne, 2008;Tabachnik, 1992) se recomiendan para entrenar la fase de máxima velocidad.…”
Section: Definición De Métodos Resistidosunclassified
See 2 more Smart Citations